HABIT training in unilateral spastic cerebral palsy children having mirror movement disorder - Javeria Shahid; Mir Arif Hussain Talpur; Hassan Rauf (Journal of the Pakistan Medical Association)
The single-arm feasibility study was planned to evaluate the therapeutic effect of hand arm bimanual intensive training in improving the fine and gross motor functions of hand, and in the reduction of intensity with respect to mirror movement disorder. The sample comprised unilateral spastic cerebral palsy children aged 6-16 years who were having mirror movement disorder and were able to make a gross grip. The hand arm bimanual intensive training was provided to the participants for 6 hours per day for 15 days for a total of 90 hours. Comparison of baseline and post-intervention showed that the functional independence level of children had improved, with improvement in unimanual and bimanual hand performance (p less than 0.05). However, there was no improvement seen in the severity of mirror movements (p>0.05).